The Effect of Earnings Management on Bank Efficiency - Mohd Fahmee Ab-Hamid; Rozilee Asid; Nor Fatimah Che Sulaiman; Wan Farisan Wan Sulaiman; Elya Nabila Abdul Bahri (2018)
A study on the effects of earnings management practices on bank cost efficiency, using banking data in five ASEAN countries, was conducted in 1989–2015. The Stochastic Frontier Analysis technique employed to gauge cost efficiency revealed that each country has different efficiency level. With panel data analysis, we further discovered that increase in earnings management practices reduces bank's efficiency significantly. It is suggested that banking supervisors and managers should formulate strategies that focus on cost efficiency–related initiatives and regulate earnings management practices. Such strategies could potentially facilitate the economic integration of ASEAN countries.